2015
DOI: 10.1080/16506073.2015.1022596
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility study on Combining Internet-Based Cognitive Behaviour Therapy with Physical Exercise as Treatment for Panic Disorder—Treatment Protocol and Preliminary Results

Abstract: Internet-based cognitive behaviour therapy (ICBT) is a recommended, cost-effective and efficacious treatment for panic disorder (PD). However, treatment effects in psychiatric settings indicate that a substantial proportion fail to achieve remission. Physical exercise improves symptoms in patients with PD, and acts through mechanisms that can augment the effect of ICBT. The feasibility of combining these two interventions has not previously been investigated, and this was the aim of this study. The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Since all the participants were able to complete the questionnaires, the Agoraphobic Cognition Questionnaire (ACQ), part of the standard packet used in panic anxiety research together with the BSQ [29, 40], was added to the questionnaire packet to allow for a more comprehensive assessment of panic-related symptomatology in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all the participants were able to complete the questionnaires, the Agoraphobic Cognition Questionnaire (ACQ), part of the standard packet used in panic anxiety research together with the BSQ [29, 40], was added to the questionnaire packet to allow for a more comprehensive assessment of panic-related symptomatology in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital Anxiety and Depression Scale (HADS) [36], the Body Sensation Questionnaire (BSQ) [37], and the Mobility Inventory of Agoraphobia-Alone (MI-A) [37] describe levels of anxiety, depression, panic-related symptoms, and avoidance behaviour. They have all shown satisfactory internal consistency and clinical cut-offs established (HADS 12 points, MI-A 1.65 points, and BSQ 2.31 points) [37–40]. A modified version of the Panic Attack Scale (PAS) [28] presents frequency and experienced severity of markedly increased bouts of dizziness.…”
Section: Methodsmentioning
confidence: 99%
“…We included eight studies with a total of 431 subjects for the planned meta-analysis (Bischoff et al, 2018;Cromarty et al, 2004;Gaudlitz et al, 2015;Hovland et al, 2015;Jacquart et al, 2017;McEntee and Halgin, 1999;Merom et al, 2008;Schwartz and Kaloupek, 1987). Figure 1 displays the selection of studies from a total of 11,437 articles identified through systematic search.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Sabourin, Stewart, Watt, and Krigolson (this issue) showed that running as interoceptive exposure followed by a 3-day group CBT intervention reduces AS. Hovland, Johansen, Sjøbø, Vøllestad, Nordhus, Pallesen, Havik, Martinsen, and Nordgreen (this issue) describe a feasibility study on combining internet-based cognitive behavior therapy with physical exercise as treatment for panic disorder. Their preliminary results suggest combined treatment is both feasible and beneficial.…”
mentioning
confidence: 99%